2022
DOI: 10.3390/jcm11051374
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Cage Subsidence in Single-Level Lateral Lumbar Interbody Fusion

Abstract: We investigated the incidence and clinical features of cage subsidence after single-level lateral lumbar interbody fusion (LLIF). We studied a retrospective cohort of 59 patients (34 males, 25 females; mean age, 68.9 years) who received single-level LLIF. Patients were classified into subsidence and no-subsidence groups. Cage subsidence was defined as any violation of either endplate, classified using radiographs and computed tomography (CT) images. After one year, we compared patient characteristics, surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…Therefore, this score is not a good predictor for cage subsidence in OLIF surgery and demonstrates low accuracy (0.695). Previous studies have reported that Hounsfield units calculated by qCT may help assess bone quality more accurately than the DEXA T-score [ 9 , 34 ]. Notably, low Hounsfield units indicate low BMD, which further indicates a higher incidence of developing cage subsidence [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this score is not a good predictor for cage subsidence in OLIF surgery and demonstrates low accuracy (0.695). Previous studies have reported that Hounsfield units calculated by qCT may help assess bone quality more accurately than the DEXA T-score [ 9 , 34 ]. Notably, low Hounsfield units indicate low BMD, which further indicates a higher incidence of developing cage subsidence [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the revision rate of patients with cage migration accounted for 1.44%. The causes of cage migration are mainly due to obesity, getting out of bed too early, small interbody fusion cage, abnormal vertebral body shape, improper bone graft material, osteoporosis, bony endplate injury and insufficient opening of contralateral annulus [ 27 29 ]. Cage migration usually occurs after SA-LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…One week later, the author performed selective LLIF through a lateral retroperitoneal approach, as previously described [ 14 – 19 ]. Initially, the patients were positioned in a left lateral decubitus position.…”
Section: Methodsmentioning
confidence: 99%
“…With ongoing advancements in surgical techniques and instruments, anterior column realignment (ACR) using retroperitoneal lateral lumbar interbody fusion (LLIF), [ 14 16 ] combined with posterior osteotomy, has been widely adopted for the correction of spinal deformities [ 15 17 ]. LLIF is a relatively new technique that can be performed via the anterior or trans-psoas approach, allowing the surgeon to access the disc space [ 14 , 18 , 19 ]. In general, ACR is performed first in combined anterior-posterior (A-P) surgery.…”
Section: Introductionmentioning
confidence: 99%